Combined Curcuma longa and Cratoxylum formosum Extracts Possess Anti-liver Cancer and Anti-HBV Activities in HepG2.2.15 - Jevapatarakul, Damita; Thienprasert, Nattanan Panjaworayan T; Payungporn, Sunchai (Current Traditional Medicine, 2021)
Background: Curcuma longa Linn. and Cratoxylum formosum have been consumed as the Thai traditional medicine for curing liver diseases. However, biological effects from a combination of C. longa and C. formosum have not been investigated. Objective: This study focused to investigate the effects of combined extracts on anti-liver cancer activity, anti-Hepatitis B virus (HBV) activity and alteration of miRNA expression, including their effects on p53 and NF-ΚB protein expressions. Methods: The cytotoxicity effects of hot water extract on liver cancer cells were examined by using the MTT assay. Annexin V assay and Western blot analysis were conducted to investigate the effects of plant extracts on the apoptosis pathway and cellular protein expressions. Finally, the expression of HBV genes and miRNA expressions were evaluated by using a quantitative real-time PCR. Results: The cell viability assay indicated that 400 μg/mL of combined C. longa and C. formosum extracts significantly inhibited different liver cancer cell lines without affecting a normal cell (Vero). The combined extracts could induce liver cancer cell death via the apoptosis pathway by up-regulating p53 expression while down-regulating NF-ΚB expression. Moreover, 150 μg/mL of the combined extract specifically suppressed HBx gene expression in liver cancer cells that stably express HBV proteins. However, 150 μg/mL of the combined extract had no effect on miR-34a and miR-199a/b expressions. Conclusion: This study firstly reported anti-liver cancer and anti-HBV activities of the combined C. longa and C. formosum extracts.
Keywords: liver cancer